Creating Flexibility in Teacher-Certification Policy to Ensure Quality and Equity - Ross, Flynn (Maine Policy Review, 2005)
As do many states, Maine has requirements and standards aimed at having “well-qualified” teachers. While few dispute the need for such standards, Flynn Ross brings attention to one case in Portland where use of a standardized exam to certify new teachers was preventing well-qualified—but culturally and linguistically diverse—teachers from becoming certified. She chronicles the successful attempts of one group to petition the Maine State Board of Education to allow greater flexibility in the testing standards. In doing so, she points to a larger truth that well-intentioned policy goals may seek to achieve a greater good, but may at the same time have unintended consequences.